MUSCARINIC RECEPTORS IN RAT CORTEX, HIPPOCAMPUS, HYPOTHALAMUS AND BRAIN-STEM FOLLOWING TRANSIENT FOREBRAIN ISCHEMIA AND HEMORRHAGIC-SHOCK - (:unkn) unknown (ELSEVIER IRELAND LTD, 1994)
[H-3]Quinuclidinyl benzilate binding properties of cerebral cortex, hippocampus, hypothalamus and brainstem of rats subjected to transient forebrain ischemia or severe hemorrhagic shock were investigated. Maximal binding capacities (B-max) were not significantly different from control animals in either model. On the other hand, significant increases in binding affinities at all four brain regions in the ischemia-reperfusion group and at hypothalamic and brainstem membranes in the hemorrhagic shock group were observed, K-d values obtained in colter and hippocampus of animals in shock were similar to control values. It was concluded that in brain ischemia models, the number of brain muscarinic receptors do not change at early stages, but binding affinities increase most likely due to systemic hypotension rather than reperfusion. The well-developed circle of Willis seems to protect cortical and hippocampal muscarinic receptors from hypoxia-induced changes.
Keywords: BINDING; QUINUCLIDINYL BENZILATE; FOREBRAIN ISCHEMIA; HEMORRHAGIC SHOCK; MUSCARINIC RECEPTOR; ADENOSINE-A1 BINDING-SITES; GERBIL HIPPOCAMPUS; AUTORADIOGRAPHIC ANALYSIS; LIPID-PEROXIDATION; CALCIUM-ANTAGONIST; 2ND MESSENGER; ACETYLCHOLINE; MECHANISMS; AFFINITY; CHOLINE